2019
DOI: 10.15252/embj.2018101409
|View full text |Cite
|
Sign up to set email alerts
|

Cul3‐Klhl18 ubiquitin ligase modulates rod transducin translocation during light‐dark adaptation

Abstract: Adaptation is a general feature of sensory systems. In rod photoreceptors, light‐dependent transducin translocation and Ca2+ homeostasis are involved in light/dark adaptation and prevention of cell damage by light. However, the underlying regulatory mechanisms remain unclear. Here, we identify mammalian Cul3‐Klhl18 ubiquitin ligase as a transducin translocation modulator during light/dark adaptation. Under dark conditions, Klhl18−/− mice exhibited decreased rod light responses and subcellular localization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 101 publications
1
21
0
Order By: Relevance
“…2 M Samd7 −/− , Samd11 −/− , Samd7/11 DKO, and WT control mice (n = 3) were used for the ERG study. The ERG recording method followed previously reported methods 16 . In brief, ERGs were recorded by a white LED luminescent electrode placed on the cornea (PuREC; Mayo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…2 M Samd7 −/− , Samd11 −/− , Samd7/11 DKO, and WT control mice (n = 3) were used for the ERG study. The ERG recording method followed previously reported methods 16 . In brief, ERGs were recorded by a white LED luminescent electrode placed on the cornea (PuREC; Mayo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Electroretinograms were conducted, as described previously (Chaya et al, 2019;Kozuka et al, 2019). In brief, mice were dark-adapted overnight and then we anesthetized the mice by intraperitoneally injecting 100 mg/kg ketamine and 10 mg/kg xylazine.…”
Section: Erg Recordingmentioning
confidence: 99%
“…A recent study showed that Unc119 expression levels in photoreceptors are influenced by its phosphorylation/dephosphorylation by casein kinase 2 (CK2) and the calcium regulated calcineurin (Chaya et al, 2019 ). The phosphorylation state of Unc119 affects its interaction with cullin 3-kelch-like 18 (Cul3-Klhl18) ubiquitin E3 ligase, which ubiquitinylates unphosphorylated Unc119, leading to its degradation.…”
Section: Peripheral Membrane Protein Compartmentalization Within the mentioning
confidence: 99%